Management of hepatocellular carcinoma: from bench to bedside and beyond - Cheung, Tan To (Translational Gastroenterology and Hepatology, 2019)
There have been remarkable strides in the management of hepatocellular carcinoma, thanks to the collaboration between researchers and clinicians. What used to be a straightforward open resection of the tumour can now be performed laparoscopically (1).